2018
DOI: 10.1111/1462-2920.14331
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas syringaepv. tomato exploits light signals to optimize virulence and colonization of leaves

Abstract: Light is pervasive in the leaf environment, creating opportunities for both plants and pathogens to cue into light as a signal to regulate plant-microbe interactions. Light enhances plant defences and regulates opening of stomata, an entry point for foliar bacterial pathogens such as Pseudomonas syringae pv. tomato DC3000 (PsPto). The effect of light perception on gene expression and virulence was investigated in PsPto. Light induced genetic reprogramming in PsPto that entailed significant changes in stress to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 101 publications
(157 reference statements)
1
44
1
Order By: Relevance
“…Although our previous results showed that light had a regulatory effect on the above-mentioned categories in PsPto in vitro populations (Santamaria-Hernando et al, 2018), we show here that the contact with the leaf triggers a regulatory response that is upstream to the regulatory effect exerted by light. Interestingly, we have found that following contact with the leaf surface, and regardless of light conditions, all genes that encode the chemosensory cluster III are up-regulated in PsPto (Tables S1 and S2).…”
Section: Discussioncontrasting
confidence: 76%
See 4 more Smart Citations
“…Although our previous results showed that light had a regulatory effect on the above-mentioned categories in PsPto in vitro populations (Santamaria-Hernando et al, 2018), we show here that the contact with the leaf triggers a regulatory response that is upstream to the regulatory effect exerted by light. Interestingly, we have found that following contact with the leaf surface, and regardless of light conditions, all genes that encode the chemosensory cluster III are up-regulated in PsPto (Tables S1 and S2).…”
Section: Discussioncontrasting
confidence: 76%
“…Record GSE10 1783 (Santamaria-Hernando et al, 2018) previously generated in our laboratory has been used for comparisons.…”
Section: Data Ava I L a B I L I T Y S Tat E M E N Tmentioning
confidence: 99%
See 3 more Smart Citations